Role of Rhizosphere Bacteria Isolated from Wild-type Varieties of Sundarbans to Endure Salt Tolerance (Journal of Science and Technology Research, 2023)
Bangladesh is a low-lying riverine country where a large number of populations live in the saline zone. Salinization is a burning issue around the world that affect the plant growth as well as crop production. Due to soil salinization, a fifth of the world's agricultural land has been spoiled. From the geographical setting, Bangladesh is one of the most vulnerable countries to the impact of various natural hazards and disasters. Sundarbans also experienced such natural hazards and disasters, e.g., tsunamis, floods, and cyclones every year for being its location. Moreover, the study area's salinization level is increasing daily. As a result, the plants in the study area are facing a critical situation due to the rapidly changing saline levels. The study attempted to analyze rhizosphere bacteria isolated from wild-type varieties of Sundarbans to endure salt tolerance. This study was conducted using primary and secondary data. Wild-type variety and soil samples were collected from the Sundarbans. To isolate salt-tolerant bacteria, different concentrations of salt were used. The salt tolerance isolates were used to observe the role of seed germination and plant growth. The isolated salt-tolerant bacteria showed their effects on plant growth and seed germination in saline soil. Bacillus and Acinetobacter bacterial species were identified using 16S rRNA gene sequencing, which promoted plant growth and seed germination at a high salt level. Since rhizosphere bacteria play an essential role in enduring salt tolerance, it can be a straightforward and eco-friendly strategy to reduce plant salt stress.J. of Sci. and Tech. Res. 4(1): 71-80, 2022